Promoting creative imaginative learning for fine art education students in the 21st century - Zulfi Hendri (Imaji, 2022)
The development of science, technology, and art, and changes in the socio-cultural environment must be managed properly by the practitioners of fine art education at universities in preparing future art teachers. Learning methods that have been believed to be appropriate by lecturers must be reviewed, managed, and oriented to scientific truth and student needs. Today's art learning must prioritize creative imagination to the current level of development, so that later students will be professionally competent in their fields. The use of a creative imaginative approach is due to the fact that in art learning there is a relationship between the stages of the creative process (preparation, incubation, illumination, verification) and the psychological product of creating fine art. With creative imaginative learning models for art education students, the works made will always have novelty in ideas, forms, and techniques as one of the main goals of 21st century education that emphasizes the creativity development.Keywords: creative imaginative learning, art education Mewujudkan pembelajaran yang imajinatif kreatif bagi mahasiswa pendidikan seni rupa di abad 21AbstrakPerkembangan ilmu pengetahuan, teknologi, dan seni,  serta perubahan lingkungan sosial-budaya, harus disikapi  dengan baik oleh penyelenggara pendidikan seni rupa di perguruan tinggi dalam menyiapkan calon guru seni rupa. Cara-cara pembelajaran yang selama ini diyakini benar oleh dosen harus ditelaah ulang, disesuaikan dan diorientasikan pada kebenaran ilmiah serta kebutuhan mahasiswa. Pembelajaran seni rupa sekarang ini harus mengutamakan kepada imajinasi kreatif sampai pada tingkat perkembangannya yang kekinian, sehingga kelak mahasiswa memiliki kompetensi dalam bidangnya secara profesional. Penggunaan pendekatan yang imajinatif kreatif dikarenakan dalam pembelajaran seni rupa ada hubungan antara tahap-tahap proses kreatif (persiapan, inkubasi, iluminasi, verifikasi) dan produk psikologis berkarya seni rupa. Dengan model pembelajaran yang imajinatif kreatif bagi mahasiswa pendidikan seni rupa, maka karya yang diciptakan akan selalu memiliki kebaruan dalam ide/gagasan, bentuk, dan teknik yang menjadi salah satu tujuan utama pendidikan abad 21 yang menekankan pengembangan kreativitas.Kata kunci: pembelajaran imajinatif kreatif, pendidikan seni rupa